The Work Environment and Its Influence on the Management of Imminent Childbirths by Midwives in Morocco: An Ecosystemic Approach to Maternal Health - Bouazza, Ghizlane; Boualam, Abderrahmane; DAHOU, Badreddine; Elaazia, Rachid; Mohammed, Belomaria; Touil, Driss; Chakhtoura, Khalid; Soufiani, Abdelati (Bangladesh Journal of Medical Science, 2025)
Objectives This cross-sectional descriptive study, conducted amongst 247 midwives in the Rabat-Salé-Kenitra region (Morocco), evaluates the influence of the professional environment on the management of imminent childbirths. The ecosystemic approach adopted considers the work environment as a major determinant of obstetric care quality. Result Results reveal that whilst 63% of participants received specific training, only 38% feel fully prepared to manage these emergency situations. Multivariate analysis identifies professional experience (adjusted OR=5.42; 95% CI: 2.73-10.76; p<0.001) and regular access to resources (adjusted OR=3.78; 95% CI: 1.95-7.34; p<0.001) as independent predictors of perceived preparedness. Work overload (adjusted OR=0.41; 95% CI: 0.24-0.71; p=0.002) and absence of protocols (adjusted OR=0.35; 95% CI: 0.16-0.78; p=0.009) are significantly associated with lower professional confidence. Conclusion These findings highlight the importance of a holistic approach integrating workplace environment optimisation, professional skills enhancement, and infrastructure improvement to ensure safe and sustainable obstetric care. BJMS, Vol. 24 No. 03 July’25 Page : 889-897